Addressing Inheritance and Divorce Disputes in Deathbed Situations: A Maslahah-Based Study of South Africa’s Muslim Minority - Abduroaf, Muneer; Ceres, Mogamat Soliegh (Universitas Islam Sultan Agung, 2024)
South Africa features a blend of legislative regulations, customary laws, and evolving legal principles. This dynamic becomes especially complex for the small Muslim community, which must also adhere to Islamic Law, particularly in matters of inheritance distribution. Currently, South African legal references regarding inheritance under Islamic law are limited. This article seeks to analyze a specific inheritance case in which a husband, on his deathbed, has two wives, a son, and a daughter. The first wife was divorced while he was on his deathbed, and during this period, he married another woman before ultimately passing away. In his will, the husband stipulated that the estate should be distributed according to Islamic law, thus entitling his legitimate wife to inheritance. This study employs descriptive qualitative research using scenario-thinking methods to explore potential future outcomes for which no legal precedent exists. In analyzing this case, the concept of public interest (maslahah) emerges as a relevant theory aligned with the principle of justice. Various scholarly opinions from Islamic legal schools were also utilized in the analysis. The article recommends that the South African Muslim Judicial Council prioritize maslahah, proposing that both wives share 3/24 of the estate, the son receive 14/24, and the daughter receive 7/24. Although this decision has not yet been formally recognized in Islamic law, it can be viewed as an act of independent reasoning (ijtihad) based on the principle of justice through the approach of public interest without specific textual evidence (maslahah mursalah). Additionally, rationalized public interest (maslahah ma’qul al-ma’na) was applied to allocate inheritance to the first wife, acknowledging her extended time with the deceased husband.